Cultivating onion under drought stressed condition - Ghodke, Pranjali H; Thangasamy, A; Mahajan, V; Gupta, A J; Singh, Major (Indian Horticulture, 2019)
Drought stress adversely affects onion crop yield and quality. Onion bulb crop can withstand the water deficit stress during its vegetative and bulb maturity stage but act as highly sensitive during its bulb enlargement stage resulting into tremendous yield losses. Similarly, reproductive stage is also highly sensitive stage to drought stress limiting the onion seed production and quality. The most effective way to address this challenge is to identify the promising drought tolerant genotypes, traits and incorporating in existing onion cultivar by various crop improvement programs. Awareness and training programs for farmers for adapting the new technologies and cultural practices are some of the additional strategies for mitigating the climate change challenges in onion crop.